Inhibition of complement activation by CD55 overexpression in human induced pluripotent stem cell derived kidney organoids - Gaykema, Lonneke H.; van Nieuwland, Rianne Y.; Dekkers, Mette C.; van Essen, Mieke F.; Heidt, Sebastiaan; Zaldumbide, Arnaud; van den Berg, Cathelijne W.; Rabelink, Ton J.; van Kooten, Cees (Frontiers in Immunology, 2023)
End stage renal disease is an increasing problem worldwide driven by aging of the population and increased prevalence of metabolic disorders and cardiovascular disease. Currently, kidney transplantation is the only curative option, but donor organ shortages greatly limit its application. Regenerative medicine has the potential to solve the shortage by using stem cells to grow the desired tissues, like kidney tissue. Immune rejection poses a great threat towards the implementation of stem cell derived tissues and various strategies have been explored to limit the immune response towards these tissues. However, these studies are limited by targeting mainly T cell mediated immune rejection while the rejection process also involves innate and humoral immunity . In this study we investigate whether inhibition of the complement system in human induced pluripotent stem cells (iPSC) could provide protection from such immune injury. To this end we created knock-in iPSC lines of the membrane bound complement inhibitor CD55 to create a transplant-specific protection towards complement activation. CD55 inhibits the central driver of the complement cascade, C3 convertase, and we show that overexpression is able to decrease complement activation on both iPSCs as well as differentiated kidney organoids upon stimulation with anti HLA antibodies to mimic the mechanism of humoral rejection.